God, beyond me : from the I's absolute ground in Hölderlin and Schelling to a contemporary model of a personal God - Woezik, Cia van. (Critical Studies in German Idealism, 2010)
German idealism has attempted to think an absolute ground to self-conscious I-hood. As a result it has been theologically disqualified as pantheistic or even atheistic since many maintain that such a ground cannot be reconciled with a personal God. In the early writings of Friedrich Schelling (1775-1854), it is clear that he and his contemporaries were aware of this difficulty. His Tübinger fellow student, Friedrich Hölderlin (1770-1843), was convinced of the ultimate inadequacy of any philosophical system to grasp the unitary ground of all that is and turned to poetry. The metaphysical insights expressed in his poetry have been largely neglected in both philosophical and theological scholarship. Drawing on the 20th century metaphysics of Dieter Henrich and Karl Rahner, this book elaborates on Hölderlin's poetry. This results in a novel concept of God as both unitary and personal ground of I-hood.